What Can Parasites Tell Us About the Pathogenesis and Treatment of Asthma and Allergic Diseases - Bohnacker, Sina; Troisi, Fabiana; de los Reyes Jiménez, Marta; Esser-von Bieren, Julia (Frontiers in Immunology, 2020)
The same mechanisms that enable host defense against helminths also drive allergic inflammation. This suggests that patho-mechanisms of allergic diseases represent evolutionary old responses against helminth parasites and that studying anti-helminth immunity may provide insights into patho-mechanisms of asthma. However, helminths have developed an intricate array of immunoregulatory mechanisms to modulate type-2 immune mechanisms. This has led to the hypothesis that the lack of helminth infection may contribute to the rise in allergic sensitization in modern societies. Indeed, the anti-inflammatory potential of helminth (worm) parasites and their products in allergy and asthma has been recognized for decades. As helminth infections bring about multiple undesired effects including an increased susceptibility to other infections intended helminth infection is not a feasible approach to broadly prevent or treat allergic asthma. Thus, the development of new helminth-based biopharmaceutics may represent a safer approach of harnessing type-2-suppressive effects of helminths. However, progress regarding the mechanisms and molecules that are employed by helminths to modulate allergic inflammation has been relatively recent. The scavenging of alarmins and the modulation of lipid mediator pathways and macrophage function by helminth proteins have been identified as important immunoregulatory mechanisms targeting innate immunity in asthma and allergy. In addition, by regulating the activation of dendritic cells and by promoting regulatory T-cell responses, helminth proteins can counter-regulate the adaptive Th2 response that drives allergic inflammation. Despite these insights, important open questions remain to be addressed before helminth molecules can be used for the prevention and treatment of asthma and other allergic diseases.